ANALISIS PENGARUH MODERASI KUALITAS AUDIT PADA HUBUNGAN HARGA PASAR SAHAM DAN GOODWILL DI INDONESIA - Marsudi, Almatius Setya (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
The study on intangible assets, goodwill in particular, becomes an interesting topic to reinvestigate since question about the relevance value is often discussed recently. This research aims to test the relevance value of goodwill information and see the effect of moderation variable of audit quality on the relevance value of goodwill. The research was conducted on the companies listed in Indonesia Stock Exchange with regression analysis. The value model of stock exchange as the function from Book Value and Earning was used and the content analysis was conducted when assessing the goodwill of company.With 71 non-financial companies in Indonesia as the samples, this research shows the result that the goodwill has a significant negative relation on stock price.  It was also proven that the audit quality improves the relevance value of goodwill. This improvement makes the role of auditor important in assessing the accurate goodwill value.